Pengaruh Waktu Ageing Dan Kecepatan Pengadukan Pada Sintesis Hidroksiapatit Dari Cangkang Telur Dengan Metode Presipitasi - Rio Andika; Ahmad Fadli; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite (HAp) is one of the calcium phosphate compounds are used as biomaterials because of the ceramic material which has a stable properties. The purpose of this study is to study the effect of ageing time and stirring rate of the HAp obtained. HAp from eggshells has been successfully synthesis using precipitation method with variation of ageing time and stirring rate. Eggshells were calcined at 1000 oC for 5 hours to produce calcium oxide (CaO). CaO was dissolved into nitric acid (HNO3) to obtain (Ca(NO3)2), and then mixed slowly into a diamonium hydrogen phosphate solution which was already dissolved into aquabidest. After mixing process is complete, the solution was settling with the variation of ageing time 0 hour, 12 hours, 36 hours and 48 hours and the best condition continued in the second variation of the stirring rate 200 rpm, 250 rpm, 350 rpm and 400 rpm. HAp produced at the ageing time 12 hours is the optimum condition. Bonds of PO43- and OH- shown HAp compounds, also it contained tricalcium phosphate (TCP) and calcium hydroxide (Ca(OH)2) compounds. Morphology of HAp particles had a granular form with a increasing particle size of HAp with the ageing time in the range 60-48 nm, whereas the faster rate of stirring had been produced the particle in the range 47-44 nm.Keywords: ageing time; eggshells, hydroxyapatite; mixing; precipitation